Web Based Dashboard of Airplane Turbulence Mitigation - Ghozali, Ahmad Lubis; Kuresih, Kuresih; Cahyanto, Kurnia Adi; Iryanto, Iryanto; Gernowo, Rahmat (Al-Makki Publisher, 2024)
Airplane accidents still occur frequently, one of which is caused by turbulence. To minimize the risk, an effective forecasting system is needed. This research focuses on developing a web-based dashboard for aircraft turbulence mitigation by considering factors such as convective cloud growth, Richardson number index, and wind shear. The dashboard was developed through four steps: requirement analysis, design, implementation, and verification. The Richardson number index (Ri) is calculated using a formula involving temperature and wind speed at different geopotential heights. Alert status is determined based on Ri values and other parameters, with three alert levels: 'Alert 1', 'Alert 2' and 'Alert 3'. The system provides alerts based on user input. If the cloud cover is less than 50%, the “Alert 1” status is displayed; if Ri < 0.25, the “Alert 2” status appears; and if the wind shear exceeds the threshold, the “Alert 3” status indicates that flights are prohibited. Pilot tests show that the system works well and the Ri calculation results are comparable to existing Richardson calculators. The dashboard allows users to access critical information related to turbulence and flight status in real-time, thereby improving flight safety. Timely alerts help in flight-related decision making. This research successfully developed a web-based dashboard for aircraft turbulence mitigation that works well. By monitoring convective cloud growth, Richardson number index, and wind shear, the system is able to provide relevant alerts to improve flight safety.